Miriam K. Young papers - Young, Miriam K., 1921-2011.
Correspondence, a 1945 issue of WAC News : the Army Gal's Publication, printed matter, family papers, photographs, and other papers relating chiefly to Young's service with the U.S. Army Women's Army Corps during World War II. Pertains to her work as a laboratory technician with the Manhattan Project at Los Alamos, N.M. Includes a plastic-encased piece of trinitite, melted rock from the Trinity Site, N.M., where the atomic bomb was first tested.
Bank clerk. Served with the U.S. Army Women's Army Corps assigned to the Manhattan Project's Los Alamos facility where she worked with the Experimental Physics Group. Married name: Miriam K. Young-Krollman.
Collection material in English.
Keywords: United States. -- Army. -- Women's Army Corps; United States. -- Army. -- Women's Army Corps -- Periodicals; Manhattan Project (U.S.); WAC news : the Army gal's publication; Atomic bomb -- Testing; World War, 1939-1945 -- Women -- United States; World War, 1939-1945 -- New Mexico -- Los Alamos; Trinity Site (N.M.); Bank clerks